Novel Fumarate Hydratase Mutation in Siblings With Early Onset Uterine Leiomyomas and Hereditary Leiomyomatosis and Renal Cell Cancer Syndrome. (May 2018) - Gunnala, Vinay; Pereira, Nigel; Irani, Mohamad; Lilienthal, Debra; Pirog, Edyta C.; Soslow, Robert; Caputo, Thomas A.; Elias, Rony; Kligman, Isaac; Rosenwaks, Zev
Abstract : Hereditary leiomyomatosis renal cell cancer syndrome is an autosomal dominant disorder characterized by uterine and cutaneous leiomyomas and increased predisposition to renal cell carcinoma, papillary type II. The syndrome is caused by heterozygous mutations to the fumarate hydratase ( FH ) gene located on chromosome 1. Affected females generally present with early onset, atypical uterine leiomyomas and cutaneous findings, however, delays in diagnosis are very common in patients with isolated uterine findings. We present a case series of 2 sisters in their 20s who presented with isolated uterine leiomyomas and were found to carry a novel mutation for the fumarate hydratase gene. One patient was referred for treatment of infertility and recurrent miscarriages and the other was referred for acute symptomatic anemia due to myomas. Prompt diagnosis of hereditary leiomyomatosis renal cell cancer was made due to a high index of clinical suspicion based on early onset disease and familial clustering as well as characteristic pathologic findings on uterine leiomyoma surgical specimen. Timely diagnosis not only allowed for genetic counseling and renal cancer surveillance, but also for fertility counseling given the increased morbidity associated with uterine leiomyoma due to hereditary leiomyomatosis and renal cell cancer syndrome.